URANIUM (VI) SORPTION ON COLLOIDAL MAGNETITE UNDER ANOXIC ENVIRONMENT: EXPERIMENTAL STUDY AND SURFACE COMPLEXATION MODELLING - Missana T.; Garcia-Gutierrez M.; Fernndez V. (My University, 2003)
Magnetite is one of the most important end member of iron corrosion products under a reducing environment; therefore, it may be one of the first products interacting with radionuclides in a radioactive waste disposal after the canister failure.Nanocrystalline magnetite was synthetised in the laboratory and its main physico-chemical properties (microstructure, surface area, surface charge) were analysed. The stability of the oxide was also investigated under the experimental conditions used in sorption studies. The sorption behaviour of UVI onto magnetite was analysed under O2- and CO2-free conditions in a wide range of pH, ionic strengths and radionuclide concentrations.The uranyl binding to magnetite is characterised by a sorption edge between pH 4 and 5.5, and sorption was found to be independent on the electrolyte concentration, which indicates the formation of inner sphere complexes. The sorption isotherms showed a linear behaviour up to the saturation of the sorption sites with a Langmuir-type behaviour.One of the aims of this work was to find the simplest model capable to reproduce the experimental data. Sorption data were fitted using a classical approximation (diffuse double layer model), considering only one type of surface site and evaluating two different options: the first one involving two different monodentate complexes, and the second one a single binuclear bidentate complex. A highly satisfactory fit of the experimental data was obtained by both approaches in the range of the experimental conditions investigated.